Anthropogenic introduction of the Spotted Barb, Barbodes binotatus, across the Wallace Line in western Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Astuti SS, Hariati AM, Kusuma WE, Yuniarti A, Kurniawan N, Wiadnya DGR. 2023. Anthropogenic introduction of the Spotted Barb, Barbodes binotatus across the Wallace Line in western Sulawesi, Indonesia. Biodiversitas 24: 1713-1722. Barbodes binotatus (Valenciennes, 1842) is a native freshwater fish species in the western part of Indonesia, ranging from Sumatra, Borneo, Java, and Bali Islands to the east in the Wallacea region as far as Lombok and Sumbawa Islands. We reported the first record of its occurrence in other Wallacea regions, especially in the western part of Sulawesi Island. Thirty specimens were captured from the Salu Salibo and Lantora Rivers during the field survey. Morphological examinations and genetic confirmation by DNA barcoding approach provided accurate and reliable identification for B. binotatus. The DNA data suggested that the existence of B. binotatus in the western part of Sulawesi Island, across the Wallace Line, is due to human introduction. The human introduction of non-native species, such as B. binotatus, may cause a severe decline in native ichthyo-biodiversity in Sulawesi Island. We, therefore, suggest that further studies are important to mitigate the negative consequences of this supposedly introduced species on the island.
Keywords: Wallacea, invasive species, COI, nucleotide BLAST, phylogenetic tree